Hydrogeophysical investigation of the impact of invasive tree species on groundwater at the Dayspring Children's Village, South Africa - Ngobeni, David Dillon (My University, 2014)
Dayspring Children’s Village, which is located about 66 km northwest of Johannesburg, has been experiencing a chronic shortage of water for over 30 years. Five out of seven boreholes that are scattered within the school property are dry and there is evidence of contamination in one of the two wells that are producing water at two depths. The presence of bluegum (Eucalyptus globulus) trees is suspected to be the principal cause for the depletion of the aquifer(s) because of their documented high rate of transpiration. The purpose of this project is to determine the complex interaction between the plants and structural elements of the various aquifers, site wells for clean water, and assist with explaining the existing contamination. This study involved parallel studies by other students. My focus was the use time-lapse DC resistivity to map preferential pathways of groundwater so that the impact of the bluegum trees could be determined. Other geophysical studies included time-domain electromagnetics, gravity and magnetics. These methods were used to map geological contacts, lithologies, geological structures, and the distribution of groundwater. Hydrogeology results from a parallel study have shown that there at least two aquifer system at Dayspring School. Time-lapse resistivity and gravity measurements were collected towards the end of rainy season and towards the end of dry season. The results show that groundwater at Dayspring School is largely structurally controlled. The impact of the bluegum trees is not obvious, but it was concluded that the trees are not the cause of apparent groundwater depletion because their root lengths do not reach the mapped geologic structures.
Keywords: Groundwater - South Africa - Dayspring Children's Village.; Eucalyptus globulus - South Africa.; Plant-water relationships - South Africa - Johannesburg.